2013
DOI: 10.2139/ssrn.2207804
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management, Capital Structure and the Role of Institutional Environments

Abstract: This paper examines the effect of earnings management on financial leverage and how this relation is influenced by institutional environments by employing a large panel of 25,798 firms across 37 countries spanning the years 1989 to 2009. We find that firms with high earnings management activities tend to have high corporate leverage. More importantly , this positive relation is attenuated by strong institutional environments. Our results lend strong support to the agency theory of free cash flow. Various robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 25 publications
8
48
0
2
Order By: Relevance
“…The leverage (in line with An et al, 2013), sales growth (as observed by Dechow, Hutton, Kim, & Sloan, 2012), and ROA (as observed by Silva, Weffort, Flores, & Silva, 2014;McNichols, 2000;and Kothari et al, 2005) variables exhibit, statistically, a significant and positive effect on the level of earnings management.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The leverage (in line with An et al, 2013), sales growth (as observed by Dechow, Hutton, Kim, & Sloan, 2012), and ROA (as observed by Silva, Weffort, Flores, & Silva, 2014;McNichols, 2000;and Kothari et al, 2005) variables exhibit, statistically, a significant and positive effect on the level of earnings management.…”
Section: Resultsmentioning
confidence: 75%
“…Schipper (1989) had already found this relationship, suggesting that this intentional intervention in the financial reporting process could generate private gains. An, Li, and Yu (2013) also analyzed the effect of EM in financial leverage. The study aimed to verify how the EM/leverage relationship is influenced by institutional environments.…”
Section: Earnings Managementmentioning
confidence: 99%
“…To mitigate the impact of omitted variables on our conclusions, we must first find a suitable instrumental variable not directly correlated with corporate R&D innovation but able to directly influence a firm's real estate ownership. For this purpose, we follow the method of Lin et al (), Chen (), and An et al () by using average industry‐year‐city real estate ownership ( Meanrevalue ) as the IV of corporate real estate ownership.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review made to the related literature of earnings management phenomenon, and the prior related researches, it is apparent, that some prior researches found no relationship between the capital structure and the phenomenon of earnings management (Mozarpour and Norouzi, 2015) (An, Li, and Yu, 2013) (Zamri, Abdul Rahman, and Isa, 2013) (Roodpohti and Chashmi, 2011), whereas other showed that this relation exists (Uwuigbe, Ranti, and Bernard, 2015) (Benkraiem, 2012) (Tahir, 2011) (Zhang and Liu, 2009), despite that among which, some declared that this relation is positive, while others declared that it is negative. These different findings must be considered incentives for authors and academics for more investigations of the phenomenon of earnings management in different countries, especially the developing countries.…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%